Clinical usefulness of the free web-based image analysis application ImmunoRatio for assessment of Ki-67 labelling index in breast cancer. Issue 8 (15th March 2017) - Yeo, Min-Kyung; Kim, Hee Eun; Kim, Sung Hun; Chae, Byung Joo; Song, Byung Joo; Lee, Ahwon
Abstract : Aims: Ki-67 is a prognostic marker in breast cancer; however, the use of the Ki-67 labelling index (LI) in clinical practice requires a consistent and easily accessible scoring method. The present study evaluated the use of the free internet-based image analysis program ImmunoRatio to score Ki-67 LI in breast cancer in comparison with manual counting. Methods: Ki-67 immunohistochemical detection was performed in 577 breast cancer cases, and the Ki-67 LI was determined by ImmunoRatio and manual counting. Results: The Ki-67 LI determined by ImmunoRatio correlated well with that obtained by manual counting. The concordance rate between ImmunoRatio and manual counting was excellent (κ coefficient of 0.881) at a Ki-67 LI cut-off value of 20%. Cases with high Ki-67 LI by ImmunoRatio were associated with poor overall survival, in particular in the hormone receptor positive group. Conclusions: The web-based automated image analysis program ImmunoRatio is an attractive alternative to manual counting to determine the Ki-67 LI in breast cancer.